1992
DOI: 10.5032/jae.1992.04017
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Enrollment In Agricultural Science And Membership In The FFA In Texas

Abstract: Beginning with A Nation at Risk in 1983, numerous reports were issued throughout the 1980s calling for educational reform in the United States. These reports resulted in sweeping educational reforms enacted by state legislatures nationwide. In Texas, significant educational changes were initiated in 1984 by House Bill 72. One of the outcomes of this bill was major reform in secondary agricultural education. In 1988, the traditional program of Vo-Ag I, II, III, and IV was phased out and replaced with twentythre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Similar to findings from previous studies (Reis & Kahler, 1997;Luft & Geise, 1991), this investigation identified parents to be the most influential individuals on a students' decision to enroll in an urban agricultural education program, however, friends and significant others were considered to be less of an influence. This study also identified an interest in animals to be an influential factor for student enrollment behaviors supporting the findings of Reis and Kahler (1997), Marshall, Herring, and Briers (1992), and Luft and Geise (1991), although, these studies defined interests more broadly.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar to findings from previous studies (Reis & Kahler, 1997;Luft & Geise, 1991), this investigation identified parents to be the most influential individuals on a students' decision to enroll in an urban agricultural education program, however, friends and significant others were considered to be less of an influence. This study also identified an interest in animals to be an influential factor for student enrollment behaviors supporting the findings of Reis and Kahler (1997), Marshall, Herring, and Briers (1992), and Luft and Geise (1991), although, these studies defined interests more broadly.…”
Section: Discussionsupporting
confidence: 78%
“…Past studies have indicated numerous factors influencing student enrollment behaviors including parents, friends, and significant others (Luft & Geise, 1991;Marshall, Herring, & Briers, 1992;Reis & Kahler, 1997); circumstantial/disavowance reasons (Marshall, Herring, & Briers, 1992); interests (Connors, Moore, & Elliot, 1989;Marshall, Herring, & Briers, 1992); image, future value, and perceptions of agriculture (Hoover & Scanlon, 1991;Talbert & Larke, 1995); and career and educational preparation, developmental skills, academic enhancement, response to social pressure, and participation in activity enhanced learning (Sutphin & Newsom-Stewart, 1995). Although these studies have identified numerous factors influencing enrollment in secondary programs of agriculture, there has been limited research efforts focused on students enrolled in secondary agricultural programs within urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument was field tested at two schools that had ethnic diversity and were not in the study. The original constructs were developed through a literature search and previous questionnaires by Flores (1989) and Marshall (1990). Scales to measure these constructs were developed based on both conceptual and empirical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research involving the FFA has focused on identifying leadership characteristics and differences between FFA members and non-FFA members in regional areas and states (Townsend & Carter, 1982;Ricketts & Newcomb, 1984;Stewart, Smith, Ehlert, & Milhalevich, 1985;Scanlon & Burket, 1986;Fraze, 1986;Marshall, 1990;Dormody & Seevers, 1994;Wingenbach & Kahler, 1997). These studies support the theory that "all good leaders are learners" (Frigon & Jackson, 1996) and that the FFA organization has a successful leadership program.…”
Section: Ffa Studiesmentioning
confidence: 99%